Crown and branch attributes of mid-aged Betula alnoides plantations in response to planting density. Issue 8 (17th November 2017) - Wang, Chun-Sheng; Zeng, Ji; Hein, Sebastian; Zhao, Zhi-Gang; Guo, Jun-Jie; Zeng, Jie
ABSTRACT: Both crown and branch characteristics greatly affect tree growth and timber quality, and their development is closely related to planting density (PD). Here crown and branch attributes of Betula alnoides were investigated in a 14-year-old experimental plantation in southern China with five planting densities ranging from 500 to 3333 stems per hectare (sph). The results showed that high PD significantly reduced crown and branch sizes. The ratios of crown diameter to stem diameter at breast height at the stand level and for dominant and co-dominant trees were almost constant regardless of PD. PD also had no significant influence on the number and angle of branches, and only planting with the highest density significantly increased branch density and mortality. Insertion angle (IA) of dead branches was greater than that of live branches and these differences were significant at the two low planting densities (833 and 500 sph). Linear mixed models revealed that branch diameter (BD) was negatively correlated with its relative height in the crown and IA. The binary-logistic regression model indicated that branch status (live or dead) was codetermined by BD and PD. These findings can help farmers cultivate high-quality wood of B. alnoides and obtain a higher economic return.